Downregulation of the Na(+)-creatine cotransporter in failing human myocardium and in experimental heart failure. - Neubauer, S; Remkes, H; Spindler, M; Horn, M; Wiesmann, F; Prestle, J; Walzel, B; Ertl, G; Hasenfuss, G; Wallimann, T (1999)
BACKGROUND:The failing myocardium is characterized by depletion of phosphocreatine and of total creatine content. We hypothesized that this is due to loss of creatine transporter protein. METHODS AND RESULTS:Creatine transporter protein was quantified in nonfailing and failing human myocardium (explanted hearts with dilated cardiomyopathy [DCM; n=8] and healthy donor hearts [n=8]) as well as in experimental heart failure (residual intact left ventricular tissue, rats 2 months after left anterior descending coronary artery ligation [MI; n=8] or sham operation [sham; n=6]) by Western blotting. Total creatine content was determined by high-performance liquid chromatography. Donor and DCM hearts had total creatine contents of 136.4+/-6.1 and 68.7+/-4.6 nmol/mg protein, respectively (*P<0.05); creatine transporter protein was 25.4+/-2.2 optical density units in donor and 17.7+/-2.5 in DCM (*P<0.05). Total creatine was 87.5+/-4.2 nmol/mg protein in sham and 65.7+/-4.2 in MI rats (*P<0.05); creatine transporter protein was 139.0+/-8.7 optical density units in sham and 82.1+/-4.0 in MI (*P<0.05). CONCLUSIONS:Both in human and in experimental heart failure, creatine transporter protein content is reduced. This mechanism may contribute to the depletion of creatine compounds and thus to the reduced energy reserve in failing myocardium. This finding may have therapeutic implications, suggesting a search for treatment strategies targeted toward creatine transport.